2007
DOI: 10.1111/j.1745-7262.2007.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aortic endothelium ultrastructure in male rats following castration, replacement with testosterone and administration of 5α-reductase inhibitor

Abstract: These results suggest that low concentrations of T and DHT are associated with ultrastructural damage of the aortic endothelia in male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Additionally, testosterone may promote a nongenomic effect potentially induced directly in the absence of a receptor, through a nontranscriptional effect, or by a distinct nonclassical receptor that is possibly associated with the plasma membrane [46]. It was reported that testosterone deprivation in rats, submitted to castration or to 5 α -reductase inhibitor treatment (inhibits the conversion of testosterone to dihydrotestosterone), produced injuries in aortic ECs detected by electron microscopy [47]. ECs ultrastructure in orchidectomized animals seemed severely crimpled, coarse, and protuberant; with ruined cell-cell connections, and adhesion of red blood cells to the surface.…”
Section: Testosterone Endothelial Health and Erectionmentioning
confidence: 99%
“…Additionally, testosterone may promote a nongenomic effect potentially induced directly in the absence of a receptor, through a nontranscriptional effect, or by a distinct nonclassical receptor that is possibly associated with the plasma membrane [46]. It was reported that testosterone deprivation in rats, submitted to castration or to 5 α -reductase inhibitor treatment (inhibits the conversion of testosterone to dihydrotestosterone), produced injuries in aortic ECs detected by electron microscopy [47]. ECs ultrastructure in orchidectomized animals seemed severely crimpled, coarse, and protuberant; with ruined cell-cell connections, and adhesion of red blood cells to the surface.…”
Section: Testosterone Endothelial Health and Erectionmentioning
confidence: 99%
“…It was also demonstrated that androgen deficiency contributes to endothelial damage in a castrated rat model (Lu et al 2007). Furthermore, investigations showed that testosterone and dihydrotestosterone upregulate nitric oxide synthase (NOS) expression and activity in male genital tissues, particularly in cavernous tissue (Lugg et al 1995;Marin et al 1999;Penson et al 1996;Zvara et al 1995).…”
mentioning
confidence: 99%
“…The median serum concentration of total testosterone was 17.0 nmol l 21 , SHBG was 40.7 nmol l 21 , BT was 7.29 nmol l 21 and FT was 0.29 nmol l 21 . The geometric mean CCS was 36.665.0, which was calculated using the following equation: exp [mean (log CCS)].…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Additionally, testosterone could stimulate endothelial progenitor cells, which plays a key role in endothelial repair. 19,20 Lu et al 21 have proposed that decreased testosterone is associated with ultrastructural damage of the aortic endothelium. In this regard, hypogonadism has been reported to contribute to the development of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%